The Pselaphinae (Coleoptera: Staphylinidae) of Madagascar. VI. Description of Ambohitantella banari gen. et sp. n. with notes on Nearticerodes Jeannel, 1954 and Triceratomerus Jeannel, 1960 - Hlaváč, Peter; Nakládal, Oto (Zootaxa, 2016)
A new genus and a new species, Ambohitantella banari gen. et sp. n., from Madagascar (Ambohitantely Special Reserve) is described. The diagnosis is given for related genera Triceratomerus Jeannel, 1960 and Nearticerodes Jeannel, 1954. The lectotype is designated for Triceratomerus sparsepunctatus Jeannel, 1960. An identification key to genera of malagasy Clavigerodina with 3-segmeneted antennae is provided.